THE POLITICS OF ASSIMILATION AND IT’S AMBIVALENCE: the Mozambican experience - Mindoso, André Victorino (Universidade Federal da Bahia, 2021)
The paper analyses the politics of assimilation that characterized the social and political thinking of the ruling elite of the State in Mozambique, from the modern colonialism to the socialist revolution of the 1970s and 1990s. Inspired on the sociology of modernization and assimilation, it analyzes texts of some members of the intellectualized high ruling elite of the State, namely Armindo Monteiro, Adriano Moreira, Joaquim da Silva Cunha, EduardoMondlane, Aquino de Bragança and Sérgio Vieira. It suggests that the politics of assimilation is presenton the thinking of these elite. The most significant aspect of such a policy consisted on proposing a project of society aiming at integrate all individuals, based on the modern idea of homogenization of racial, ethnic, tribal and linguistic particularities. Such a pretension has revealed its ambivalence by excluding those social sectors that proposed to integrate.